Dietary magnesium and risk of cardiovascular and all-cause mortality after myocardial infarction: A prospective analysis in the Alpha Omega Cohort - Evers, Ilse; Cruijsen, Esther; Kornaat, Iris; Winkels, Renate M.; Busstra, Maria C.; Geleijnse, Johanne M. (Frontiers in Cardiovascular Medicine, 2022)
Background: An adequate intake of magnesium has been associated with lower risks of cardiovascular disease (CVD) and all-cause mortality in population-based studies. Whether an adequate magnesium intake is important for reducing long-term mortality risk after myocardial infarction (MI) is not yet clear. Objective: We examined magnesium intake in relation to CVD, all-cause and coronary heart disease (CHD) mortality, on top of drug treatment, in patients who had experienced an MI. Methods: We included 4,365 Dutch patients aged 60-80 y from the Alpha Omega Cohort with a history of MI <10 y before study enrollment. Dietary data over the past month were collected at baseline using a 203-item validated food frequency questionnaire from which magnesium intake was calculated. Patients were followed for cause-specific mortality through December 2018. HRs for mortality in tertiles of energy adjusted magnesium intake were obtained from multivariable Cox proportional hazard models, adjusting for age, sex, education, obesity and other lifestyle and dietary factors. Associations were also studied in relevant subgroups, including patients with diabetes and diuretics users. Restricted cubic splines were used for studying the continuous association of magnesium intake with CVD mortality. Results: The average magnesium intake was 302 ± 78 mg/day and 28% of male and 33% of female patients had adequate intakes. Magnesium containing supplements were used by 5.4% of the cohort. During a median follow-up of 12.4 years (48,473 person-years), 2035 patients died, of which 903 from CVD and 558 from CHD. Higher magnesium intakes (>320g/d), compared to the reference group (<283 mg/d), were associated with a lower risk of CVD mortality (HR: 0.72; 95% CI: 0.54 – 0.98) and all-cause mortality (HR: 0.78; 95% CI: 0.64 – 0.95) in the fully adjusted model. A non-significant inverse association was found for CHD mortality. Associations for CVD mortality were slightly stronger in diuretic users (HR: 0.55; 95% CI: 0.34 –0.89). Results were similar after excluding magnesium supplement users. Conclusion: An adequate intake of magnesium may be important for lowering long-term mortality risk after MI, especially in patients treated with diuretics. The Alpha Omega Trial was registered at clinicaltrials.gov as NCT03192410.